An Analysis of Visual Metaphor to Understand Creativity in Contemporary Art - Alghathami, Rihab Abdullah (Journal of Humanities & Social Sciences, 2023)
This study handles the revelation of the concept of visual metaphor in contemporary arts and the relationship of the borrowed material to the idea to be expressed by the artworks. This is achieved by analysing a number of contemporary artworks by several Saudi artists. The study also aims to elaborate the relationship that links the idea to the material in their works in addition to revealing the philosophy of creativity in the contemporary product, providing a critical reading of contemporary artworks, and emphasizing the importance of visual metaphor being the basic structure in the contemporary artworks. The research adopts the descriptive-analytical method to reveal the visual metaphors as a contemporary work on its own, and explain the concept of visual metaphor representing it in artworks and introducing a definition for it. Among the results reached to by the study is that creativity is achieved when the visually borrowed material to build a contemporary artwork is linked to the idea and signifies it. In addition, understanding the relationships linking the target field to the meaning field in an artwork contributes to the recipient’s understanding of the process of artistic creativity. The study recommends the need for deep study and analysis of visual metaphor in contemporary arts, beside conducting similar studies and research to the current study to discover the creative idea in the production of the contemporary visual artist.